Dissecting Brainstem Locomotor Circuits: Converging Evidence for Cuneiform Nucleus Stimulation - Chang, Stephano J.; Cajigas, Iahn; Opris, Ioan; Guest, James D.; Noga, Brian R. (Frontiers in Systems Neuroscience, 2020)
There is a pressing and unmet need for effective therapies for freezing of gait (FOG) and other neurological gait disorders. Deep brain stimulation (DBS) of a midbrain target known as the pedunculopontine nucleus was proposed as a potential treatment based on its postulated involvement in locomotor control as part of the mesencephalic locomotor region (MLR). However, DBS trials fell short of expectations, leading many clinicians to abandon this strategy. Here, we discuss the potential reasons for this failure and review recent clinical data along with preclinical optogenetics evidence to argue that another nearby nucleus, the cuneiform nucleus, may be a superior target.